1991
DOI: 10.1002/jsfa.2740570103
|View full text |Cite
|
Sign up to set email alerts
|

Influence of supranutritional vitamin E supplementation in the feed on swine growth performance and deposition in different tissues

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
56
3
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 23 publications
13
56
3
1
Order By: Relevance
“…32±35 In the present study, feeding RD diets as opposed to diet CONT had no in¯uence on pig plasma enzyme activities, suggesting no damaging effect of dietary full-fat rapeseed on pig tissues. It has previously been reported that supplementation of vitamin E-adequate diets had no effect on plasma enzyme activities in pigs, 20 and in the present study, supplementation of RD diets had no effect on plasma enzyme activities. Similarly, the AT concentration in diets with no supplementary ATA (diets CONT and RD0) was apparently suf®cient to prevent oxidative damage to tissue in vivo despite the increase in unsaturated fatty acid content of tissue lipids of pigs fed the RD diets.…”
Section: Plasma Enzyme Activitiescontrasting
confidence: 46%
See 2 more Smart Citations
“…32±35 In the present study, feeding RD diets as opposed to diet CONT had no in¯uence on pig plasma enzyme activities, suggesting no damaging effect of dietary full-fat rapeseed on pig tissues. It has previously been reported that supplementation of vitamin E-adequate diets had no effect on plasma enzyme activities in pigs, 20 and in the present study, supplementation of RD diets had no effect on plasma enzyme activities. Similarly, the AT concentration in diets with no supplementary ATA (diets CONT and RD0) was apparently suf®cient to prevent oxidative damage to tissue in vivo despite the increase in unsaturated fatty acid content of tissue lipids of pigs fed the RD diets.…”
Section: Plasma Enzyme Activitiescontrasting
confidence: 46%
“…Similar increases in concentration of AT in the blood plasma of pigs fed diets supplemented with ATA have been reported in a number of previous studies. 8,20,26,30,31 The AT concentrations in the plasma of pigs fed diets RD200 and RD500 were not signi®cantly different (p b 0.05), suggesting that a saturation point had been reached around a dietary intake of 200 mg ATA kg À1 diet. …”
Section: ±25mentioning
confidence: 87%
See 1 more Smart Citation
“…This agrees well with the pattern already noted for plasma AT concentrations. 13 These results are in general agreement with other studies in pigs 6,10,11,19,20,23 and suggest that at dietary levels of between 200 and 500 mg ATA kg À1 diet, tissues become saturated with AT and uptake is no longer proportional to dietary supply.…”
Section: Tissue Fatty Acid Compositionsupporting
confidence: 93%
“…There is evidence from studies with chicks and laboratory rats that very high dietary vitamin A (eg, 100 x requirement) may interfere with both vitamin E absorption and blood a-tocopherol concentration (Abawi and Sullivan, 1989;Blakely et al, 1991). The (Jensen et al, 1988;Asghar et al, 1991;Mahan, 1991;Anderson et al, 1995a, b (Blomhoff et al, 1990). However, we have previously noted a ninefold increase in liver retinol concentration at slaughter as a result of a tenfold increase in dietary level of vitamin A in a study with growing and finishing pigs (Anderson et al, 1995b …”
mentioning
confidence: 99%